In‐Situ Activated NiFePBA‐FeOOH Electrocatalyst for Oxygen Evolution Reaction and Zinc‐Air Battery. Issue 15 (21st April 2021) - Wei, Licheng; Zhang, Yufei; Yang, Yang; Ye, Minghui; Li, Chengchao
Abstract: Developing low‐price, highly efficient and durable electrocatalysts for sluggish oxygen evolution reaction (OER) is still a significant challenge for metal‐air batteries and electrochemical water splitting technology. Here, cost‐effective OER catalyst composing of nickel‐iron Prussian blue analogue and iron oxyhydroxide (NiFePBA‐FeOOH) was successfully prepared by facile hydrothermal method. Designed NiFePBA‐FeOOH catalyst exhibits superior OER performance with low overpotential, small Tafel slope and stable durability. Systematic investigations with in‐situ Raman and Transmission electron microscope reveal that the as‐prepared catalyst has undergone in‐situ electrochemical transformation to generate real catalytic active species of nickel and iron oxyhydroxides. Particularly, the assembled zinc‐air battery with NiFePBA‐FeOOH catalyst also displays a long‐term lifetime of 165 h only presenting a slight increase in voltage gap. Additionally, the successful exploration of cobalt‐iron PBAs with iron oxyhydroxides further demonstrates the universality of PBAs‐oxyhydroxides composites for energy storage and conversion applications. Abstract : A cost‐effective OER catalyst composing of nickel‐iron Prussian blue analogues and iron oxyhydroxide (NiFePBA‐FeOOH) prepared by facile hydrothermal method exhibits superior OER performance with low overpotential, small Tafel slope and steady durability, which is benefitting by the increasing specific surface area and accelerated charge transfer and the synergistic effect between in‐situ activated nickel and ion oxyhydroxides.